What causes aberrant salience in schizophrenia? A role for impaired short-term habituation and the GRIA1 (GluA1) AMPA receptor subunit. - Barkus, C; Sanderson, D; Rawlins, J; Walton, M; Harrison, P; Bannerman, D (2014)
The GRIA1 locus, encoding the GluA1 (also known as GluRA or GluR1) AMPA glutamate receptor subunit, shows genome-wide association to schizophrenia. As well as extending the evidence that glutamatergic abnormalities have a key role in the disorder, this finding draws attention to the behavioural phenotype of Gria1 knockout mice. These mice show deficits in short-term habituation. Importantly, under some conditions the attention being paid to a recently presented neutral stimulus can actually increase rather than decrease (sensitization). We propose that this mouse phenotype represents a cause of aberrant salience and, in turn, that aberrant salience (and the resulting positive symptoms) in schizophrenia may arise, at least in part, from a glutamatergic genetic predisposition and a deficit in short-term habituation. This proposal links an established risk gene with a psychological process central to psychosis and is supported by findings of comparable deficits in short-term habituation in mice lacking the NMDAR receptor subunit Grin2a (which also shows association to schizophrenia). As aberrant salience is primarily a dopaminergic phenomenon, the model supports the view that the dopaminergic abnormalities can be downstream of a glutamatergic aetiology. Finally, we suggest that, as illustrated here, the real value of genetically modified mice is not as 'models of schizophrenia' but as experimental tools that can link genomic discoveries with psychological processes and help elucidate the underlying neural mechanisms.